2021
DOI: 10.1186/s12957-021-02178-6
|View full text |Cite
|
Sign up to set email alerts
|

Chordomas and chondrosarcomas of the skull base: treatment and outcome analysis in a consecutive case series of 24 patients

Abstract: Background We present our 9-year consecutive case series of skull base chordomas and chondrosarcomas from a UK tertiary referral centre, discussing treatments offered and outcomes. This was carried out to improve understanding around current treatment and to better inform the management of future patients. Methods Consecutive case series over a 9-year period (2007–2016). Retrospective data analysis from the electronic skull base multidisciplinary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For three-fraction SRS for brain metastases, normal brain tissue V18 < 30 cc and V23 < 7 cc were associated with <10% risk of brain necrosis. Finally, we evaluate the results of this study based on the latest reports [14,[21][22][23]31,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. According to the latest reports, the 5-year local recurrence rate for chordoma was about 15 to 35%, while for chondrosarcoma, it was less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…For three-fraction SRS for brain metastases, normal brain tissue V18 < 30 cc and V23 < 7 cc were associated with <10% risk of brain necrosis. Finally, we evaluate the results of this study based on the latest reports [14,[21][22][23]31,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. According to the latest reports, the 5-year local recurrence rate for chordoma was about 15 to 35%, while for chondrosarcoma, it was less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the cavernous carotid artery [ 14 ], the internal carotid artery [ 40 ], and the cavernous carotid artery [ 14 ] could be surrounded by parasellar chondrosarcoma. Generally, intracranial chondrosarcoma is difficult to resect completely and often requires adjuvant treatment for complete control [ 41 ]. Tumors with these preoperative characteristics greatly increase the difficulty of total resection of the parasellar chondrosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Chordoma and chondroid chordoma both are immune positive for epithelial markers cytokeratin (CK) and epithelial membrane antigen (EMA), though chondrosarcoma is negative for both [28]. Chordoma show up comparable to fetal notochord on both light and electron microscopy and are immune-histochemically and ultrastructurally similar.…”
Section: Differential Diagnosismentioning
confidence: 99%